Relationship between Stock Market and Exchange Rate Intervention: Evidence from China - Wang, Yi (2021)
Abstract In China, the central bank has always been cautious about the operation of China's foreign exchange market, and government intervention in the exchange rate market has always existed. This dissertation focuses on the characteristics of the volatility spillover effect and mean spillover effect of the three under different macro environments, the transmission mechanism of foreign exchange intervention on foreign exchange expectations and stock prices, and the relationship between different transmission mechanisms on the three. It intends to figure out how to make better use of foreign exchange intervention policies to promote the further development of China’s foreign exchange market and stock market. On the basis of related theories, it establishes the transmission mechanism among foreign exchange intervention, foreign exchange expectations and the stock market and discusses the mutual transmission relationship among them. It constucts the VAR-GEARCH-BEKK model and divide the entire data interval into three stages, namely from 2013 to August 2015 (the stage before the exchange rate reform), from August 2015 to March 2018 (from the exchange rate reform to Between the China-US trade war) and March 2018 to 2020 (after the China-US trade war). It figures out that there is an index spillover effect of foreign exchange intervention in the Shanghai and Shenzhen stock markets in three stages. Through the three-stage coefficients, it can be concluded that the spillover effects of foreign exchange intervention on the Shanghai and Shenzhen stock markets are positive in three stages, indicating that the overall situation of the Chinese economy is closely related to government intervention Keywords: Stock Market; Exchange Rate Expectation; Government Intervention.